2016
DOI: 10.1001/jamapsychiatry.2016.2657
|View full text |Cite
|
Sign up to set email alerts
|

Association of Higher Cortical Amyloid Burden With Loneliness in Cognitively Normal Older Adults

Abstract: IMPORTANCE Emotional and behavioral symptoms in cognitively normal older people may be direct manifestations of Alzheimer disease (AD) pathophysiology at the preclinical stage, prior to the onset of mild cognitive impairment. Loneliness is a perceived state of social and emotional isolation that has been associated with cognitive and functional decline and an increased risk of incident AD dementia. We hypothesized that loneliness might occur in association with elevated cortical amyloid burden, an in vivo rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
139
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 186 publications
(166 citation statements)
references
References 67 publications
6
139
0
5
Order By: Relevance
“…For instance, individuals reporting feelings of loneliness or social isolation might engage to a greater extent in unhealthy behaviors (eg, physical inactivity or poor dietary choices), which in turn are associated with increased odds of developing cardiovascular diseases and cognitive impairment . Alternatively, loneliness and social isolation might appear as a response of the cognitive impairment or as a result of an underlying neuropathology leading to dementia . Consistently with this hypothesis, various longitudinal studies showed that global cognitive function and discrete cognitive domains predicted changes in perceived social isolation over time .…”
Section: Discussionmentioning
confidence: 87%
“…For instance, individuals reporting feelings of loneliness or social isolation might engage to a greater extent in unhealthy behaviors (eg, physical inactivity or poor dietary choices), which in turn are associated with increased odds of developing cardiovascular diseases and cognitive impairment . Alternatively, loneliness and social isolation might appear as a response of the cognitive impairment or as a result of an underlying neuropathology leading to dementia . Consistently with this hypothesis, various longitudinal studies showed that global cognitive function and discrete cognitive domains predicted changes in perceived social isolation over time .…”
Section: Discussionmentioning
confidence: 87%
“…This has driven inquiries to a relatively novel concept, PSI, which has also been referred to in many studies as ‘loneliness’ [3-4] and a perceived lack of social support [5]. It merges the subjective feeling of loneliness and the objective deficiencies associated with social interactions and networks [3].…”
Section: Introductionmentioning
confidence: 99%
“…For example, it may be difficult to motivate some patients to better control their diabetes or hypertension by explaining their relationship to heart disease. Yet older adults are often especially concerned about losing independence and cognition, and they may be highly motivated to address contributing factors such as loneliness and isolation . In addition, the link between social isolation/loneliness and cardiovascular health may be an additional way to provide upstream guidance to patients by focusing on their social connections.…”
Section: Epidemiologymentioning
confidence: 99%
“…Although the IOM report focused on measures of social connection and isolation, loneliness was considered a subcomponent of these measures, and several different measures of loneliness have been used to establish its relevance to health and risk for mortality. Loneliness may be easily identified using the UCLA three‐item loneliness scale (Supplementary Table S1) . Efforts are underway to incorporate this loneliness screen into EHRs.…”
Section: Epidemiologymentioning
confidence: 99%